2016
DOI: 10.1111/1348-0421.12450
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the immunological potency of Burkholderia lipopolysaccharides in endotoxemic BALB/c mice

Abstract: Lipopolysaccharide is one of the virulence factors of the soil-borne pathogens Burkholderia pseudomallei, B. thailandensis, B. cenocepacia and B. multivorans, which cause septic melioidosis (often in B. pseudomallei infections but rarely in B. thailandensis infections) or cepacia syndromes (commonly in B. cenocepacia infections but rarely in B. multivorans infections). The inflammatory responses in Burkholderia LPS-induced endotoxemia were evaluated in this study. Prior to induction, the conserved structures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 46 publications
(74 reference statements)
0
8
0
Order By: Relevance
“…We found that an injection of >100 μg/Kg LPS resulted in an abortion in approximately 60–66% of the pregnant mice. Low dose (≤100 μg/Kg) of LPS induces maternal immune activation similar to that of a chronic infection or contact with environmental allergens such as dust [16, 19, 61]. Using low-dose LPS stimulation, the rate of abortion was as low as 11% in this study.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…We found that an injection of >100 μg/Kg LPS resulted in an abortion in approximately 60–66% of the pregnant mice. Low dose (≤100 μg/Kg) of LPS induces maternal immune activation similar to that of a chronic infection or contact with environmental allergens such as dust [16, 19, 61]. Using low-dose LPS stimulation, the rate of abortion was as low as 11% in this study.…”
Section: Discussionmentioning
confidence: 72%
“…Lipopolysaccharide (LPS), a cell wall component of gram-negative bacteria, is known as an immunostimulant that elicits production of systemic inflammatory cytokines and chemokines, expansion of leukocytes in bone marrow, activation of the complement cascade, activation of the hypothalamic-pituitary adrenal (HPA) axis and enhancement of 5-HTergic and DAergic activity in the cerebrum [1618]. In rodents, maternal immune activation through bacterial infection or exposure to allergens, usually administration of LPS, during pregnancy can produce long-lasting anxiety- and ASD-like behaviors in offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that systemic cytokines, chemokines and cell adhesion molecules (CAMs) are robustly present in the blood in Burkholderia LPS-induced endotoxemic mice 14 . In this study, the levels of cytokines, chemokines, and CAMs were evaluated in the brain tissues in endotoxemic mice (the experimental design is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the performance of astrocytes (GFAP signaling) or microglia (the numbers of transitioning cells) in B. cenocepacia LPS- or B. thailandensis LPS-induced brain was more active than the expression in B. pseudomallei LPS-induced brains. The fatty acid chain length and the kinds or repeated numbers of sugar moieties in lipid A, in terms of pathogens, leads to different changes in cytokines, chemokines and CAM expression and/or in the BBB measurements such as glial and endothelial activation, vascular permeability and the changes of infiltrating cells 14 , 20 – 22 . Septicemia is the most severe form of melioidosis in both human and animals 11 , 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation